The magic of storytelling: Does storytelling through videos improve EFL students’ oral performance? - Tgk Maya Silviyanti; Diana Achmad; Fathimath Shaheema; Nurul Inayah (Universitas Syiah Kuala, 2022)
This study aimed to examine the EFL (English as a foreign language) students’ oral presentation of storytelling. The students performed retelling of narratives such as fables, legends, myths, and fairy tales using their smartphones and video recorder. The participants of the study were 19 students enrolled in the Drama in ELT (English Language Teaching) course at Universitas Syiah Kuala, Banda Aceh, Indonesia. It employed participant observation and interviews to collect data. The results of the study revealed that for non-language aspects, the lowest score was for ‘dress code’ (M=2.1), meaning that the students did not make any efforts to dress and use props that were related to the stories they were telling. While for the language aspects, the lowest score was for ‘communicative abilities with the audience’ (M= 1.2). This shows that even though the participants recorded their performance, and there was no audience watching them directly, they still faced barriers and a lack of confidence when presenting the storytelling. The interviews further supported the findings from the observation such as not being able to use appropriate props for their performance, lack of eye contact, switching voices, use of gestures, difficulty in remembering the script, and needing somebody else to do the recording for them. Therefore, the students need more practice in front of audiences to overcome the problems in the future to ensure that the use of storytelling can improve their oral performance.